Design Innovation For Calligraphy Using Reverse Engineering And CNC Machining - Jaludin, Ahmad Amin Azmi (Universiti Sains Malaysia, 2017)
Calligraphy is an art which is can be classified as one art that has the longer in age. It is started from era of dynasty in China. Meanwhile, Islamic calligraphy founded in 3200 B.C in nil's river. For so long, calligraphy becomes a letters that communicate with the people and even becomes an art. In Islamic calligraphy, it can be seen mostly in mosque. In traditional way, they create this art by using hand. They craft the calligraphy on the wall and even craft the calligraphy on the wood as a gift. Crafting calligraphy by using hand cause a lot of time taken to produce it. With the technology that available in this world, reverse engineering technique is applied where it is can be produce without needed any parameters or blueprint. Producing by using CNC machine can also become the time taken can be reduced and it can produced a better surface finish. In this project, the calligraphy will be designed and innovate by using the software design that is available which are SolidWorks and CATIA. It will also undergo with the technique of reverse engineering and producing by using CNC machine. Then, the parameters of the produced product by using reverse engineering technique will be compared with the existing product and compare the time taken between machining process and hand-crafting process. The time taken for first input which is BISMILLAH Calligraphy recorded 2 hours 35 minutes and 44 seconds while for the second input which is REVERSE ENGINEERING LAB Typography recorded 22 hours based on the simulation time. For the parameters comparison result between the existing and produced product, the second input was involved. It contains 6 distance that has been registered to be measure. The percentage different for Distance 1, Distance 2, Distance 3, Distance 4, Distance 5 and Distance 6 are 3.43%, 0.18%, 14.20%, 0.81%, 8.50% and 25.21% respectively.